2020
DOI: 10.1177/1057083720935610
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of LGBTQ+ Students in Music Education Programs Across Texas

Abstract: We examined the experiences of 95 lesbian, gay, bisexual, transgender, and queer (LGBTQ+) music education majors, along with 39 heterosexual allies, who were student members of the Texas Music Educators Association. Participants addressed curricular practices and institutional factors that lend themselves to LGBTQ+ inclusion and safety among students, faculty, and staff. We collected data through an anonymous online survey, which included questions related to LGBTQ+ students’ experiences in their programs and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Authors of research and practical articles on current classroom practices often have observed or concluded that music educators may not receive adequate preparation to teach in ways that are responsive to students’ identities, which can include (dis)ability, race, ethnicity, gender, and sexual orientation (e.g., Garrett & Spano, 2017; Hoffman, 2011; Legette, 2003; Nabb & Balcetis, 2010; Taylor et al, 2020). While some programs may include preparation to teach diverse populations as part of education coursework outside of music teacher education, undergraduate students may have difficulty making connections between their future teaching and coursework that is not music specific (see Conway, 2002, 2012).…”
mentioning
confidence: 99%
“…Authors of research and practical articles on current classroom practices often have observed or concluded that music educators may not receive adequate preparation to teach in ways that are responsive to students’ identities, which can include (dis)ability, race, ethnicity, gender, and sexual orientation (e.g., Garrett & Spano, 2017; Hoffman, 2011; Legette, 2003; Nabb & Balcetis, 2010; Taylor et al, 2020). While some programs may include preparation to teach diverse populations as part of education coursework outside of music teacher education, undergraduate students may have difficulty making connections between their future teaching and coursework that is not music specific (see Conway, 2002, 2012).…”
mentioning
confidence: 99%
“…Previous studies, such as those by Taylor et al (2020) and Nichols (2013), posit that music spaces tend to be accepting and welcoming of trans * students; however, the experiences of the participants in this research problematize that dominant narrative about the inclusivity of arts spaces in higher education. The limited previous scholarship on music major experiences highlights the challenges trans * students can face in their majors related to their relationships with others and their ability to perform to their full potential (Bartolome & Stanford, 2017;Silveira, 2019); these challenges with peers and artistic performance were also echoed by the participants of the present study who majored or minored in music.…”
Section: Discussionmentioning
confidence: 64%
“…Transitioning from university environments to music teaching positions in K–12 environments can be challenging as preservice teachers forge new teacher identities. For gay men who may feel supported within their university music programs (Taylor et al, 2020) but may be advised by older gay teachers to hide their sexuality (e.g., Paparo & Sweet, 2014; Taylor, 2018), identity negotiation may be especially challenging. These challenges can be exacerbated when students do not have the opportunity to discuss SGM issues in preservice classes (Garrett, 2012; Taylor et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…For gay men who may feel supported within their university music programs (Taylor et al, 2020) but may be advised by older gay teachers to hide their sexuality (e.g., Paparo & Sweet, 2014; Taylor, 2018), identity negotiation may be especially challenging. These challenges can be exacerbated when students do not have the opportunity to discuss SGM issues in preservice classes (Garrett, 2012; Taylor et al, 2020). Although findings in this study are limited, they do provide evidence that in some schools, living openly without the burden of compartmentalization is possible.…”
Section: Discussionmentioning
confidence: 99%